Respuesta :

The two equations given in the question are
x = y + 10
And
x = 2y + 3
Now let us substitute the value of x in the second equation with that of the first equation. We get
x = 2y + 3
y + 10 = 2y + 3
y - 2y = 3 - 10
- y = - 7
y = 7
Now putting the value of y in the first equation, we get
x = y + 10
   = 7 + 10
   = 17
So the value of x comes out to be 17 and the value of y comes out to be 7.
Plug x= y+10 in x= 2y+3, we have:
y+10= 2y+3
⇒ 10- 3= 2y-y
⇒ 7= y

x= y+ 10= 7+ 10= 17

Final answer: x= 17, y= 7~
ACCESS MORE